A review of solar hybrid photovoltaic-thermal (PV-T) collectors and systems - Herrando, Maria; Wang, Kai; Huang, Gan; Otanicar, Todd; Mousa, Osama Bany; Agathokleous, Rafaela; Ding, Yulong; Kalogirou, Soteris A.; Ekins-Daukes, Ned; Taylor, Robert A.; Markides, Christos N. (My University, 2023)
In this paper, we provide a comprehensive overview of the state-of-the-art in hybrid PV-T collectors and the wider systems within which they can be implemented, and assess the worldwide energy and carbon mitigation potential of these systems. We cover both experimental and computational studies, identify opportunities for performance enhancement, pathways for collector innovation, and implications of their wider deployment at the solar-generation system level. First, we classify and review the main types of PV-T collectors, including air-based, liquid-based, dual air–water, heat-pipe, building integrated and concentrated PV-T collectors. This is followed by a presentation of performance enhancement opportunities and pathways for collector innovation. Here, we address state-of-the-art design modifications, next-generation PV cell technologies, selective coatings, spectral splitting and nanofluids. Beyond this, we address wider PV-T systems and their applications, comprising a thorough review of solar combined heat and power (S–CHP), solar cooling, solar combined cooling, heat and power (S–CCHP), solar desalination, solar drying and solar for hydrogen production systems. This includes a specific review of potential performance and cost improvements and opportunities at the solar-generation system level in thermal energy storage, control and demand-side management. Subsequently, a set of the most promising PV-T systems is assessed to analyse their carbon mitigation potential and how this technology might fit within pathways for global decarbonization. It is estimated that the REmap baseline emission curve can be reduced by more than 16% in 2030 if the uptake of solar PV-T technologies can be promoted. Finally, the review turns to a critical examination of key challenges for the adoption of PV-T technology and recommendations.
Keywords: Photovoltaic-thermal (PV-T); Collectors; Systems; Hybrid Solar